High Temperature Protective Coatings for Aeroengine Applications - Jopek, Jakub; Mokrzycka, Magdalena; Góral, Marek; Koscielniak, Barbara; Ochal, Kamil; Drajewicz, Marcin (Manufacturing Technology Journal, 2023)
Nickel superalloys are the main materials used in manufacturing of turbine blades and vanes in aero-space industry. They works is extremely high temperature in a corrosive environment (oxidation, hot corrosion) and undergo several different thermo-mechanical loads. Aluminide coatings are the main method of protection of the surface of nickel superalloys against exhaust gasses environment in jet en-gine. In presented article the microstructural characterization of aluminide coatings produced using two industrial methods (pack cementation and out of pack was conducted. The commercially available powders manufactured by Oerlikon-Metco were used in aluminizing process using industrial Bernex BPX Pro 325S CVD system. The MAR M247 was used as a base material. Amount of activator and pure aluminum had a noticeable effect on the total thickness of obtained layers. Both samples with increased activator and pure aluminum content formed 5 to 11.5 x thicker aluminide coatings in comparison to other sample, which was aluminized using an Al-Co powder as aluminum source. Further investiga-tions are needed to specify precise phase composition of analyzed coatings.
Keywords: Aluminide coatings; Turbine blades; MAR M247; CVD